2021
DOI: 10.3390/cancers13143413
|View full text |Cite
|
Sign up to set email alerts
|

A Prospective Real-World Multi-Center Study to Evaluate Progression-Free and Overall Survival of Radiotherapy with Cetuximab and Platinum-Based Chemotherapy with Cetuximab in Locally Recurrent Head and Neck Cancer

Abstract: Treatment options of locoregional recurrent head and neck squamous cell cancer (HNSCC) include both local strategies as surgery or re-radiotherapy and systemic therapy. In this prospective, multi-center, non-interventional study, patients were treated either with platinum-based chemotherapy and cetuximab (CT + Cet) or re-radiotherapy and cetuximab (RT + Cet). In the current analysis, progression-free survival (PFS) and overall survival (OS) were compared in patients with locoregional recurrence. Four hundred s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 21 publications
0
4
0
Order By: Relevance
“…Other two studies have reported that the 1-year OS of Cmab + RT were 44 and 47.5%, respectively (10,11). The overall response rate (ORR) in these reports was 16-58%, which was different from previous study (9)(10)(11). In contrast, the 1-year OS of salvage surgery was approximately 50% (5,6) and 1-year OS of chemotherapy with Cmab (EXTREME regimen and Cmab plus paclitaxel) was approximately 40% in recurrent or metastatic (R/M) OSCC (12,13).…”
Section: Discussionmentioning
confidence: 64%
See 1 more Smart Citation
“…Other two studies have reported that the 1-year OS of Cmab + RT were 44 and 47.5%, respectively (10,11). The overall response rate (ORR) in these reports was 16-58%, which was different from previous study (9)(10)(11). In contrast, the 1-year OS of salvage surgery was approximately 50% (5,6) and 1-year OS of chemotherapy with Cmab (EXTREME regimen and Cmab plus paclitaxel) was approximately 40% in recurrent or metastatic (R/M) OSCC (12,13).…”
Section: Discussionmentioning
confidence: 64%
“…We experienced three cases of favorable locoregional control against locoregional recurrence of OSCC with Cmab + RT. In a prospective study of locoregional recurrence of HNSCC, Hecht et al reported that Cmab + RT had superior progression-free survival and overall survival (OS) compared to Cmab alone, with a 1-year OS of 53% (9). Other two studies have reported that the 1-year OS of Cmab + RT were 44 and 47.5%, respectively (10,11).…”
Section: Discussionmentioning
confidence: 99%
“…Two (patient 1 and 2 in Table 3 ) patients received additional target therapy with cetuximab after ICT failure and showed longer survival than those without therapy. Several studies ( 34 , 35 ) have shown that cetuximab can improve survival outcomes in advanced HNC. Taken together, these findings indicate that the early identification of potential poor responders to ICT and an early shift in treatment regimens to target therapy or immune therapy may improve survival outcomes in HNC.…”
Section: Discussionmentioning
confidence: 99%
“…Another FDA-approved example for treatment in recurrent or metastatic HNSCC is the immune checkpoint inhibitor Pembrolizumab, which binds to tumor cells expressing high levels of PD-L1 and achieved a response rate of ~20% in clinical trials; however, it led to hyperprogressive tumor disease in some patients [21,22]. Despite advancements in the knowledge on HNSCC epidemiology and pathogenesis, the prognosis of HNSCC remains poor, showing no significant improvement in survival rates and a high incidence of locoregional recurrence or distant metastases in more than half of HNSCC patients [2,23,24]. The critical demand for an improved understanding of therapy response and the development of new treatment options is particularly crucial for advanced-stage, HPV − cases of HNSCC [25][26][27][28].…”
Section: Introductionmentioning
confidence: 99%